Safety and efficacy of the Oxford-AstraZeneca vaccine against SARS-CoV-2 after 2nd and 3rd dose in adults: a cross-sectional study - Shahrbanoo Sedigh Sarooni; Malihe Mohammadi; Seyed Mohammad Riahi (European Journal of Translational and Clinical Medicine)
Background: The rapid global spread of the coronavirus SARS-CoV-2 and the lack of established therapeutic choices led to development of several vaccines. Our aim was to investigate the safety and effectiveness of the Oxford-AstraZeneca adenovirus vectored vaccine against SARS-CoV-2 breakthrough infections in people who were vaccinated with 2 or 3 doses of it. Methods: This cross-sectional study was conducted from February 2021 to September 2021 on 997 people, who had received at least 2 doses of the Oxford-AstraZeneca vaccine. Demographic and clinical data were recorded using a questionnaire. The effectiveness of the vaccine was calculated based on the percentage of vaccinated people with confirmed and probable cases of SARS-CoV-2 infection. SPSS software was used for data analysis, and a significance level of p < 0.05 was chosen. Results: After vaccination with the 2nd and 3rd doses, 355 (35.6%) and 26 (8.3%) participants contracted the SARS-CoV-2 infection, respectively. Breakthrough infection after the 2nd dose was significantly higher in females (p < 0.001), those with older age (p = 0.021), diabetes (p = 0.003) and hypertension (p < 0.001). Additionally, a significant correlation was found between SARS-CoV-2 infection after the 3rd dose and chronic kidney disease (p = 0.022) and a history of infection after the second dose (p < 0.001). The prevalence of vaccine side effects after the 2nd and 3rd doses was 51.7% and 13.4%, respectively. Conclusions: The effectiveness of the Oxford-AstraZeneca vaccine in preventing SARS-CoV-2 increased from 64.4% after 2 doses to 91.7% after the 3rd dose, therefore it is recommended to administer a 3rd dose to ensure strong immunity against SARS-CoV-2. Based on our data the safety of this vaccine is acceptable.